THE STUDY OF THE EFFECTIVENESS OF THE BOWEN SELF- DIFFERENTIATION COUNSELING ON MARITAL CONFLICTS ON MARRIED WOMEN IN ISFAHAN: Life Sciences-Psychology - PARVIN KARKHANEH; MARYAM FARHANG; REZVAN JAZAYERI; RASOUL SOLEIMANI; FATEMEH BAHRAMI; MARYAM FATEHIZADE (International Journal of Life Science and Pharma Research, 2022)
The purpose of this study was to investigate the effectiveness of Bowen Self- differentiate counseling on marital conflicts among married women in Isfahan. Materials & Methods: Method of present investigation was a quasi-experimental research with experimental and control groups in the pre-test and post- test stages. The statistical population was consisted of all married women in Isfahan, those who had at least one child. The subjects were 60 people who Received higher score in questionnaire of marital conflict and randomly selected and assigned to two experimental(N=30) and control group(N=30). The measure was Marital Conflicts questionnaire with seven subscales. The experimental group received eight sessions of Bowen counseling Self- differentiation group counseling. The control group received no intervention. The data were analyzed using covariance analysis. Findings: The results showed that Bowen self- differentiation group counseling were effective on marital conflicts and their dimensions among married women. Discussion & Conclusion: the effectiveness of the Bowen Self-differentiation counseling can be used in decreasing marital problems of couples.